Should Sharia Banks Go Public: Analysis Using The RGEC Method - Hanafi, Rustam; Sutapa; Ifada, Luluk Muhimatul (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Recently, the OJK has encouraged Shariah banks to go public to obtain new funding sources for business expansion, increasing corporate value and image. In fact, are Sharia Banks that go public better than non-go public. Therefore, this study aims to test whether the health of Sharia Banks that go public is better than non-go public. Observation data used 122 Sharia Banks during the 2014-2022 period. Using an independent sample t-test and RGEC health indicators, we find that Sharia Banks that go public have better health than non-go public but are not significantly different. These results also indicate why Sharia Banks go public are not as many as Conventional Banks. Sharia Banks adhere to the principle of prudence, including going public. If going public does not significantly change the health and performance of a Shariah Bank, the initiative to go public needs to be careful because ownership will transfer to shareholders. It will be a problem if shareholders do not understand Sharia principles.